Parameter retrieval of aircraft wake vortex based on its max–min distribution of Doppler velocities measured by a Lidar. Issue 20 (30th August 2019) - Gao, Hang; Li, Jianbing; Chan, P.W.; Hon, K.K.
Abstract : Aircraft wake vortex is a sort of turbulence generated by a flying aircraft. It has attracted much attention in aviation safety area because it may cause a following aircraft to roll out of control. This study proposes a simple method to retrieve the characteristic parameters of an aircraft wake based on the max–min distribution of Doppler velocity over a RHI (range‐height indicator). First, the vortex cores are determined by the Doppler velocity's cross‐over structure. Second, the circulations are obtained by the velocity differences between the points above the vortex core and the corresponding below ones. During this process, the impact of background wind can be well mitigated. Basically, the new method is with a low computation cost and an acceptable accuracy. Its good performance has been verified by simulations and field detection data recorded in Hong Kong International Airport.